Comparing the results of one‐session, two‐session, and three‐session MSWO preference assessments. Issue 2 (19th January 2021) - Conine, Daniel E.; Morris, Samuel L.; Kronfli, Faris R.; Slanzi, Crystal M.; Petronelli, Abigail K.; Kalick, Lindsay; Vollmer, Timothy R.
Abstract : The multiple‐stimulus‐without‐replacement (MSWO) preference assessment is commonly used in behavior‐analytic research and practice. As originally published, the MSWO included 5 sessions in an effort to confirm stimulus preferences. Subsequent researchers have evaluated the validity of MSWO outcomes when the assessment is abbreviated. Generally, valid outcomes have been noted for 3‐session MSWOs (that is, the outcomes match those of the 5‐session version), while validity outcomes for 1‐ or 2‐session MSWOs have varied across studies. The current study utilized data from 157 MSWO preference assessments conducted in previously published research with 49 total participants and analyzed the extent to which 1‐session or 2‐session variations of those assessments would have yielded similar outcomes as a 3‐session assessment. Results indicate that the hierarchies produced by both abbreviated formats were strongly correlated with those produced by a 3‐session assessment. However, neither 1‐ nor 2‐session MSWOs reliably identified the same highest‐preferred stimuli as a 3‐session MSWO.